Effect of food availability and habitat characteristics on the abundance of the torrent duck during the early breeding season in the Central Andes, Argentina - Alvarez, Leandro M. (2014)
Torrent Ducks (Merganetta armata) inhabit rivers and streams across the Andes. The species feedsmainly on aquatic invertebrates and occurs in rivers with high flow rate, large emergent rocks, and low anthropogenicdisturbance. The objective of this work was to study the effect of food availability and environmental variables on theabundance of Torrent Ducks in two streams with different levels of anthropic disturbance and diverse environmentalconditions. To describe each stream, we recorded density and richness of benthic macroinvertebrates and physical-chemicalvariables, and characterized the stream habitats. We also censused the number of Torrent Ducks present in each stream. Weprepared a principal component analysis to portray features of each stream. Generalized linear models were used to estimatewhich environmental variables were associated with the ducks? abundance and to explore variations in biotic variablesbetween streams and between sections within each stream. We recorded 40 individuals in the stream with the lowestdisturbance (Arroyo Grande) and four individuals in the most highly disturbed stream (Rı´o Blanco). Variation in abundanceof Torrent Ducks was better explained by a higher density of Notoperla, Plecoptera (an aquatic insect associated with cleanwaters) and to a lesser extent by flow rate.